Longitudinal predictors of alcohol use and problems during the COVID-19 pandemic in an at-risk veteran sample - Angela J. Zaur; Dongho Shin; Jasmine Lewis; Robert A. Perera; William C. Walker; Amma Agyemang; Tara Austin; Cooper Hodges; Sarah L. Martindale; Mary Jo Pugh; Ananda B. Amstadter; Christina M. Sheerin (European Journal of Psychotraumatology, 2025)
Background: Individuals with pre-existing heavy alcohol use, prior traumatic exposures, and psychiatric disorders were considered an at-risk group for increased alcohol use and problems in the context of the COVID-19 pandemic.Objective: This study recruited from a multi-centre longitudinal cohort study of US military service members/veterans with combat exposure to examine the trajectories of alcohol use and problems in the context of a prolonged stressor.Methods: Individuals who endorsed heavy drinking and completed a measure of PTSD symptoms prior to the pandemic were invited to participate in a longitudinal survey study at three time points, three months apart, during the second year of the pandemic. Participants (N = 44) completed surveys assessing alcohol consumption and alcohol-related problems (via the AUDIT), PTSD symptoms (via the PCL-5), and infection mitigation behaviours (via a COVID-19 specific survey). Random intercept models were fitted to the longitudinal data for each of these outcomes, covarying for demographics, pandemic quarantine/physical distancing experience, pre-pandemic baseline alcohol consumption and PTSD symptoms, and time-varying alcohol consumption and alcohol-related problems as well as PTSD symptoms.Results: We did not find an increase in alcohol consumption or problems over time. However, pre-pandemic alcohol consumption predicted alcohol consumption over time (B = 0.52, SE = 0.11, p < .01). Time-varying alcohol consumption and PTSD symptoms predicted alcohol problems over time (B = 0.84, SE = 0.18, p < .01; B = 0.04, SE = 0.02, p < .05, respectively).Conclusions: Findings highlight the relevance of pre-existing hazardous alcohol consumption prior to stressors as well as ongoing consumption and PTSD symptoms as risk factors for alcohol-related problems. Findings captured more chronic impacts of pandemic stressors and demonstrated that heavy drinking and PTSD are notable risk factors for alcohol-related problems even if in the context of stabilizing, albeit still high, alcohol use.